Penyelesaian Perkara Pidana Menurut UU No. 1 Tahun 2023 - Khansa’ Ranawati Sulaiman (CV. Lenggogeni Data Publishing, 2024)
Abstract Law No. 1 of 2023 concerning the Implementation of Online Criminal Trials has regulated procedures for resolving criminal cases via online or electronic channels. This law regulates procedures, mechanisms and other provisions relating to online criminal trial processes. The process of resolving criminal cases according to Law No. 1 of 2023 starts from the initial examination stage to the final decision. The initial examination stage is carried out by investigators which is then continued with the investigation. After the investigation is complete, the public prosecutor can name a suspect or stop the case if sufficient evidence is not found. If a suspect is identified, the prosecutor will prepare an indictment and register the case with the court. After being registered with the court, the case will proceed to the trial stage. Trials are conducted online and are regulated in this law. Apart from that, there are several case resolution mechanisms, such as peacekeeping, mediation and restorative justice, which can also be done online. One of the important provisions in this law is the right for defendants or plaintiffs to access and obtain information related to trials online. Apart from that, this law also regulates the protection of human rights during the criminal trial process which is carried out online. In the event that there is an error in the trial process which is carried out online, this law also provides a solution by regulating the review procedure. This is done to ensure that the court decision given is the right and fair decision..